INTEGRASI NILAI-NILAI ISLAM WASATHIYYAH DAN NASIONALISME DI MADRASAH IBTIDAIYAH NEGERI (MIN) 15 MAGETAN - Imam Muddin (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2020)
Abstract: The mainstreaming of Islam that is specifically in the context of Islamic education in Indonesia lately can be seen from the efforts of the Ministry of Religion through the Directorate of Curriculum, facilities, institutions, and students (KSKK) Madrasas in formulating 12 mainstay programs. With this follow-up program it is hoped that an understanding of the concept of Islamic wasathiyah will be created in accordance with the Islamic character of the archipelago. The world of education is a place in shaping the character of the generations of this nation. Moreover, this nation is faced with the threat of radical religious understanding carried out by a group of persons and the disintegration of the nation. Because the process of integrating values ​​in the concept of Islamic wasathiyyah and nationalism with character education in madrasas is very necessary. The process can be done from three sides, namely: through classroom learning, madrasa culture, and extracurricular activities. Similarly, what has been done in MIN 15 Magetan. The integration process is carried out with these three activities. Pengarusutamaan Islam yang wasathan khususnya dalam konteks pendidikan Islam di Indonesia akhir-akhir ini bisa dilihat dari upaya Kemenag melalui Direktorat Kurikulum, sarana, kelembagaan, dan kesiswaan (KSKK) Madrasah dalam merumuskan 12 program andalan. Dengan adanya program tindak lanjut tersebut diharapkan terciptanya pemahaman konsep Islam wasathiyah yang sesuai dengan watak keislaman Nusantara. Dunia pendidikan merupakan wadah dalam membentuk karakter generasi-generasi bangsa ini. Terlebih bangsa ini dihadapkan dengan ancaman pemahaman agama yang radikal yang dilakukan oleh sekelompok oknum dan dis integrasi bangsa. Oleh karena proses integrasi nilai-nilai di dalam konsep Islam wasathiyyah dan nasionalisme dengan pendidikan karakter di madrasah sangatlah diperlukan. Proses tersebut bisa dilakukan dari tiga sisi yaitu: melalui pembelajaran di kelas, budaya madrasah, dan kegiatan ekstrakurikuler. Begitu pula yang telah dilakukan di MIN 15 Magetan. Proses integrasinya dilakukan dengan tiga kegiatan tersebut.